유방의 침윤성 관암종에서 색소원제자리부합화에 의한 C-erbB-2 종양유전자 증폭과 세포주기 조절단백 발현의 연관성 - 박봉근(Bong Keun Park); 김범규(Beom Gyu Kim); 차성재(Sung Jae Cha); 박성준(Sung Jun Park); 임현묵(Hyun Muck Lim); 박성일(Sung Il Park); 이태진(Tae Jin Lee) (Annals of surgical treatment and research, 2006)
Purpose: Gene amplification and/or over-expression of the c-erbB-2 are linked with poor prognosis in breast cancer. There has been only a few reports about the connection of c-erbB-2 oncogene amplification with cell regulatory proteins such as p27kip1, cyclin D1, Rb, and E2F-1. The purpose of this study is to determine the correlation the amplification of the c-erbB-2 oncogene and protein expressions of p27kip1, cyclin D1, Rb, and E2F-1. Methods: Using Chromogenic in situ Hybridization (CISH) the amplification the c-erbB-2 oncogene were determined from paraffin sections of 48 infiltrating duct carcinomas (IDC). The protein expressions of p27kip1, cyclin D1, Rb, and E2F-1 were studied immunohistochemically. Results: Among the 48 evaluated IDC patients, amplifications of the c-erbB-2 oncogene by CISH were observed in 14 cases (29.1%). The amplification of the c-erbB-2 oncogene showed a significant correlation with tumor size and stage (P=0.0001 and P=0.001). The proteins of p27kip1, cyclin D1, Rb, and E2F-1 were expressed by IHC in 23 cases (47.9%), 17 cases (35.4%), 27 cases (56.3%), and 22 cases (45.8%), respectively. Down- regulation of protein expressions showed a significant correlation with tumor size (P=0.031) in p27kip1 and estrogen and progesterone receptor status (P=0.026 and P=0.001) in Rb. The expression of the E2F-1 protein showed a significant correlation with tumor size, stage, and histologic grade (P=0.003, P=0.030, and P=0.036). The amplification of the c-erbB-2 oncogene between down-regulation of p27kip1 protein and E2F-1 protein showed a statistically significant correlation. Conclusion: The amplification of the c-erbB-2 oncogene may be correlation with cell cycle regulatory proteins such as p27kip1 and E2F-1. (J Korean Surg Soc 2006;70:14-24) KCI Citation Count: 0